Deteksi Resistensi Oseltamivir Influenza A (H1N1pdm09) dari Pasien Infeksi Saluran Pernafasan Akut Berat di Indonesia tahun 2014 - Setiawaty, Vivi; Pawestri, Hana Apsari; Susilarini, Ni Ketut (Jurnal Kefarmasian Indonesia, 2016)
Influenza viruses are classified into subtypes based on two surface antigens known as hemagglutinin (HA) and neuraminidase (NA). Antigenic changes of influenza virus can cause resistance to antiviral drugs which is already limited in variation. Resistance to the drugs used recently are due to antigenic drift by point mutation in a single amino acid at position 275 (H275Y). The purpose of this research is to identify the presence of influenza virus A (H1N1pdm09) that were resistant to oseltamivir from cases of severe acute respiratory infection (SARI)in Indonesia in 2014 by using a rapid detection test. Detection of oseltamivir resistance in NA gene is to identify the single nucleotide polimorphism (SNP) at position 275 (H275Y) using the real-time RT-PCR method from clinical specimens SARI case. A total of 870 specimens from six sentinel hospitals were collected and 15 of them positive H1N1pdm09. Of the 15 clinical specimens, H1N1pdm09 virus strains that have mutations H275Y were not found. Based on this finding, it can be concluded that during the year 2014, there is no influenza virus A (H1N1pdm09) resistant to oseltamivir from SARI cases specimen in six sentinel hospitals in Indonesia.